2021
DOI: 10.1016/j.heliyon.2021.e06720
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum ferritin is associated with oxidized low-density lipoprotein in prediabetes patients: A pilot study

Abstract: This pilot study aimed to determine if increased serum ferritin (SF) is associated with cardiovascular risk factors in patients with prediabetes. Methods: Eighteen patients with prediabetes and 36 subjects without prediabetes (control), non-white Hispanic, non-indigenous origin, Mexican mestizo descent were included. Participants had no inflammation, or vascular complications. SF and metabolic markers were evaluated in both groups. Results: SF and oxidized low-density lipoprotein (oxLDL) were increased in pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…32 Hyperglycemia was also recognized to promote oxidative stress. 33 In addition, the correlations between dyslipidemia and elevated hepcidin 34 and ferritin 35,36 levels were documented, and different populations of hypertensive patients experienced elevated ferritin levels. 37,38 Although ferritin levels are generally increased in HD patients in comparison to healthy individuals, 39 the present study showed increased ferritin levels in patients with EPO resistance and in subgroups with MetS when compared with corresponding subgroups without MetS.…”
Section: Discussionmentioning
confidence: 99%
“…32 Hyperglycemia was also recognized to promote oxidative stress. 33 In addition, the correlations between dyslipidemia and elevated hepcidin 34 and ferritin 35,36 levels were documented, and different populations of hypertensive patients experienced elevated ferritin levels. 37,38 Although ferritin levels are generally increased in HD patients in comparison to healthy individuals, 39 the present study showed increased ferritin levels in patients with EPO resistance and in subgroups with MetS when compared with corresponding subgroups without MetS.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, no changes were reported in hepatic ApoB100 with dietary iron-loading in microarray or proteomic studies. Despite this, animal models and humans exhibit an association between iron parameters and plasma VLDL and LDL (69,178,179).…”
Section: Cholesterol Synthesismentioning
confidence: 99%
“…Prediabetes is a state whereby the glucose level in blood is more than the average value but still less than the diabetes mellitus level (1)(2)(3)(4). According to the American Diabetic Association (ADA), prediabetes is diagnosed when impaired fasting glucose (IFG) level is between 100 to 125mg/dl, and impaired glucose tolerance (IGT) is between 140 to 199mg/dl (1-7).…”
Section: Introductionmentioning
confidence: 99%
“…Around 578 million people worldwide will be diagnosed with diabetes by 2030 and are expected to reach about 700 million by 2045 (12). Prediabetes patients are expected to suffer from many complications, for instance, peripheral vascular diseases, coronary artery diseases, and cerebrovascular incidents (4)(5)(6)(13)(14)(15). In other words, undiagnosed prediabetic people are at risk for developing full blown diabetes, heart attack and stroke (2,7,11,14,(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation